Hydrogeological characteristics of Hartbeespoort Dam - Davis, Aqueelah (My University, 2017)
Hartbeespoort Dam, the source of irrigation and potable water for the local community of Hartbeespoort area is a vulnerable water resource. The aim of this research was to evaluate the interaction between dam water and groundwater as well as characterise the hydrochemical data from metals and tritium. The former was done through the application of environmental isotopes and the implementation of a long term water balance, while the latter used hydrochemical data to define the spatial distribution of metals and tritium. The results indicated that the dam water is separated from the groundwater in winter. Two sources of mixing were recognized to have occurred downstream of the dam in 2015 but not in the Hartbeespoort dam area. These were identified as artificial through the runoff of agricultural water that was abstracted from the dam and through the pumping of water near the fault. Higher than normal tritium concentration indicated that contamination comes through the Crocodile River after the fault connecting the river to Pelindaba, the nuclear power generation plant south of Hartbeespoort Dam in the Broederstroom area. The Crocodile River showed that the contamination of water by lead, 22.11ppb in summer and 3.8 ppb in winter, and cadmium,2.2 ppb in winter. The Magalies River feeds the dam with copper. All metals accumulate at the dam wall and settles in the sediment, diluting the downstream water. Boreholes near the dam and spring along the fault are vulnerable to contamination. The water balance estimation resulted 18 345 472m3, with a 3.9% error, gain of water to the dam from the groundwater greater than the amount exiting the dam to through groundwater. The groundwater entering the dam is estimated to be 32 517 704m3. The groundwater exiting the dam is estimated at 14 172 232m3. The difference in groundwater showed a decrease of 10 000 000m3 over the 15 year period from 1st October 2000 until the 30th September 2015. Consequently, these results show an increased stress placed on the groundwater presumably due to an increase in groundwater abstraction from agriculture and the expanding mining area.
Thesis (M.Sc. (Hydrogeology))--University of the Witwatersrand, Faculty of Science, School of Geosciences, 2017.
Keywords: Hydrogeology; Water-supply; Groundwater; Hartbeespoort Dam (South Africa)--Research